PELATIHAN MARKETING PUBLIC RELATIONS BAGI STAKEHOLDERS PARIWISATA DI OBJEK WISATA STONE GARDEN BANDUNG BARAT - Susie Perbawasari; Yanti Setianti; Aat Ruchiat Nugraha; Dian Wardiana Sjuchro; Ayu Indra Wardhani (LPPM UMRI, 2019)
The trend of Muslim tourism continues to increase along with the awareness of Muslims to apply the Muslim lifestyle. The Muslim lifestyle affected the demands of halal tourism packages — one of the attractions that are trying to hold a halal tour package, namely Stone Garden. Several obstacles are found related to the realization of Stone Garden into halal tourist destinations, namely the limited human resources, infrastructure, facilities, and coaching patterns from the manager. To foster human resources in the activities of tourism services and tourism promotion needs to be improved through the implementation of Marketing Public Relations training for tourism destination managers in facing the challenges of the increasingly globalized tourism market. The training held at the Stone Garden Tourism Awareness Group secretariat with participants from tourism agents, tourist managers, and tour guides. The training methods used are discussion, lecture, and case simulation. The results of the training showed that the knowledge and communication skills of Marketing Public Relations communication among the actors, managers, and tour guides in the Stone Garden area experienced a considerable increase which was shown by participants understanding the importance of communication in community-based tourism management. Keywords: Marketing Public Relations, Training, Tourism, Stakeholders, Halal Tourism